Resuscitation of bacterial biofilm by sunlight : effects on different enteropathogenic bacteria - Taher, Auhona; Paromita, Progga; Choaity, Maliha Hossain (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.